Comparative bactericidal activity of four macrolides alone and combined with rifampicin or doxycycline against Rhodococcus equi at concentrations achievable in foals - Huguet, Anne-Sophie; Gourbeyre, Ophélie; Bernand, Agathe; Philibert, Charline; Bousquet-Melou, Alain; Lallemand, Elodie A.; Ferran, Aude A. (Frontiers in Pharmacology, 2024)
Rhodococcus equi causes life-threatening respiratory disease in foals. The standard treatment typically involves a combination of rifampicin and a macrolide antibiotic. Although previous studies have demonstrated the in vitro activity of these antibiotics against R. equi, the tested concentrations often do not reflect those achievable in foals. Therefore, this study was performed to evaluate the in vitro bactericidal activity of rifampicin, doxycycline, and four macrolides (clarithromycin, azithromycin, gamithromycin and tulathromycin) individually and in combination, at concentrations observed at the target site of infection in foals. Additionally, we investigated the efficacy of these antibiotics at different pH levels to replicate the conditions in the pulmonary epithelial lining fluid and within macrophages, where R. equi can reside. We assessed the activity of antibiotics against a virulent strain of R. equi by determining the minimum inhibitory concentration (MIC) and performing checkerboard and time-kill curve assays with drugs both alone and in combination. Time-kill curves with rifampicin or doxycycline demonstrated a reduction in R. equi counts by more than 3 log10 CFU/mL. Among the macrolides, tulathromycin was ineffective, while clarithromycin achieved bacterial elimination within 24 hours under both extracellular and intracellular conditions. Gamithromycin and azithromycin exhibited bactericidal activity only in extracellular conditions, with no effect on the bacteria at pH 5.8. The checkerboard assay did not reveal any strong synergistic or antagonistic effects for rifampicin or doxycycline when combined with macrolides. In time-kill curves performed with maximal local concentrations achievable in foals, the combinations of rifampicin or doxycycline with macrolides did not increase the bacterial killing rate compared with the drugs alone, except for the combination of rifampicin with azithromycin, which showed slightly faster activity. However, the lower concentrations of doxycycline and clarithromycin that might be present 24 hours after treatment in foals were effective in killing bacteria under intracellular conditions only when used in combination, and not when used alone. Our study suggests that clarithromycin can be used either alone or with doxycycline and that its use in combination with rifampicin should be discouraged. Nevertheless, further studies are required to assess the clinical efficacy and potential side effects of doxycycline in foals.